2016
DOI: 10.18632/oncotarget.8895
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification of miR-141 regulates SKA2 by an endogenous ‘sponge’ HOTAIR in glioma

Abstract: Aberrant expression of miR-141 has recently implicated in the occurrence and development of various types of malignant tumors. However whether the involvement of miR-141 in the pathogenesis of glioma remains unknown. Here, we showed that miR-141 was markedly downregulated in glioma tissues and cell lines compared with normal brain tissues, and its expression correlated with the pathological grading. Enforced expression of miR-141 in glioma cells significantly inhibited cell proliferation, migration and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…The list of significant biomarkers is growing in an astonishing manner and includes a wide range of molecules such as lncRNAs and microRNAs (e.g. HOTAIR and miR-141), and several DNA repair genes (Boccard et al, 2015;Bian et al, 2016;Reon et al, 2016), which are importantly correlated with genome stability and will be explored in more detail in the next sections. Table 3 summarizes the main DNA repair biomarkers discussed in this review.…”
Section: Glioma Classification and Frequent Genetic Alterationsmentioning
confidence: 99%
“…The list of significant biomarkers is growing in an astonishing manner and includes a wide range of molecules such as lncRNAs and microRNAs (e.g. HOTAIR and miR-141), and several DNA repair genes (Boccard et al, 2015;Bian et al, 2016;Reon et al, 2016), which are importantly correlated with genome stability and will be explored in more detail in the next sections. Table 3 summarizes the main DNA repair biomarkers discussed in this review.…”
Section: Glioma Classification and Frequent Genetic Alterationsmentioning
confidence: 99%
“…Bian et al revealed that HOTAIR might act as an endogenous “sponge” of miR‐141 and that it regulated the derepression of SKA2. Both overexpression of miR‐141 and knockdown of HOTAIR in a mouse model of human glioma resulted in a significant reduction of tumor growth in vivo . Ke et al demonstrated that the knockdown of the long non‐coding RNA HOTAIR inhibited malignant biological behaviors of human glioma cells via the modulation of miR‐326.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the mechanism of how HOTAIRM1 functions to repress this process, we have adopted the ceRNA theory here, which emphasizes that lncRNAs act as ceRNAs to impair miRNA activity by sequestering paired miRNAs and facilitate corresponding mRNAs to function without miRNA interference 30,31. In the light of this thought, we have found that miR-3960 and its target mRNA HOXA1 are able to build a ceRNA network with lncRNA HOTAIRM1, which functionally influences DC differentiation.…”
Section: Discussionmentioning
confidence: 99%